PENGARUH FAKTOR SOSIAL EKONOMI TERHADAP PENDAPATAN PETANI PINANG - Muhammad Thamrin; Surna Herman; Fahrul Hanafi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
AbstractThe research was conducted using case study methods (case study). This study aims to determine how to influence the level of capital, labor, experience, education and age of farmers' income levels and how the feasibility of areca nut farm. Research hypotheses are tested using multiple linear regression and the method of R / C ratio (Revenue / Cost). From the research results obtained by the R-square 0.98 identifies that it is simultaneously (synchronously) no significant effect between capital, labor, experience, education and age of the areca farmers' income by 98% the rest influenced by other variables not examined. From the test results are obtained stasistik multiple R-square value of 0.99% means that overall there is a strong influence between capital, labor, experience, education and age of areca farmers' income levels, it is supported by the calculated F-value> F-table at the 95% confidence level (a 0.05) thereby H0 refused and H1 accepted. No effect of partial capital, experience and age on the level of areca farmers' income in this case is supported by the value t count> t-table, while the labor and education had no effect on the income level of farmers nut on a 95% confidence level. The results of the calculation, the nut farm viability obtained was R / C ratio of 1.82. This means that the nut farm is now worth the effort or can provide benefits.Keywords: sosial-economy, farmers' income, farmer